THE POSPONT RESULTS OF SWITCHING ON TOPIRAMAT GENERICS AT PATIENTS WITH EPILEPSY - I. G. Rudakova (Эпилепсия и пароксизмальные состояния)
Abstract: long-term results are presented for a switch from the brand formulation to generic topiramate preparations in adult patients suffering from symptomatic or cryptogenic focal epilepsy. A total of 110 study subjects (49 men and 61 women aged from 21 to 70 years) and 22 reference controls were followed up for a period of 18 – 29 months after the switch. Over half the patients had a clinical condition that was worse than at baseline. Drug-resistant epilepsy had formed in 37 % patients with a remission at baseline. Patients who had developed a remission following start-up Topamax therapy after 2 to 4 treatment attempts, at 18 – 29 months after the switch, had similar drug-resistance (р=0.803) and remission rates in the two groups. The number of anti-epilepsy medicines and their doses had to be increased in 73 % and 92 % of cases, respectively.